2019
DOI: 10.3390/s19112447
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Arousal Quantifying Perception of Safe and Unsafe Virtual Environments by Older and Younger Adults

Abstract: Physiological arousal has been increasingly applied to monitor exploration (or navigation) of a virtual environment (VE), especially when the VE is designed to evoke an anxiety-related response. The present work aims to evaluate human physiological reactions to safe and unsafe VEs. We compared the effect of the presence of handrails in the VE in two different samples, young and older adults, through self-reports and physiological data: Electrodermal activation (EDA) and electrocardiogram (ECG) sensors. After n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The preservation of positive affect that we observed may have been a result of not just the restorativeness of the 360-degree nature videos but also the novelty of VR. Indeed, past research has found psychophysiological responses to virtual environments (Jang et al, 2002;Leite et al, 2019). Incorporating heart rate variability (HRV) would be a useful next step in interrogating moodrelevant arousal because HRV is a low-cost and non-invasive measure to measure parasympathetic activation (see the model of neurovisceral integration, Thayer et al, 2009).…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
“…The preservation of positive affect that we observed may have been a result of not just the restorativeness of the 360-degree nature videos but also the novelty of VR. Indeed, past research has found psychophysiological responses to virtual environments (Jang et al, 2002;Leite et al, 2019). Incorporating heart rate variability (HRV) would be a useful next step in interrogating moodrelevant arousal because HRV is a low-cost and non-invasive measure to measure parasympathetic activation (see the model of neurovisceral integration, Thayer et al, 2009).…”
Section: Opportunities For Future Researchmentioning
confidence: 99%
“…Gamification elements are incorporated to capture the user's attention and challenge them to complete objectives [49][50][51][52][53][54]. Other studies have explored the study of emotional factors in user in a virtual reality environment, measuring the impact on the sensations experienced by the worker [55][56][57][58]. In this general context of virtual reality developments, patterns are identified: studies focus on specific scenarios, with different levels of realism (from basic to more advanced levels), with limited sets of simulated accidents.…”
Section: Virtual Reality In Construction the Next Level In The Building Site User Experiencesmentioning
confidence: 99%
“…Several studies have been developed to evaluate how spatial configurations are perceived by its users and which emotions they trigger. Leite et al show that a virtual environment is effective in evoking different reactions for safe and unsafe spaces [15]. Shemesh et.…”
Section: Immersive Virtual Realitymentioning
confidence: 99%